Knowledge and related themes in Academic research - Bendahmane, Omayma (2013)
Purpose: This research aims at performing an overview of previous research about knowledge, learning organisation and organisational learning, while focusing on finding topics of interest, trends and patterns of research, in addition to identifying gaps in literature and providing suggestions for future knowledge focused research. Methodology/approach: Data was collected by selecting papers from journals ranked two to four stars based on Association of Business Schools (ABS). Analysis was conducted using content analysis and citation analysis. Furthermore, cognitive mapping was used in order to summarise discussions and represent relationship between findings. Findings: Research within the three fields seems to attract different authors. Further, it is expected to still be of interest to researchers. The main findings of this research are:  Closely related topics: organisational performance, tacit knowledge and internal knowledge management.  Three agreed upon enablers: trust, communication, and motivation.  Gaps in literature: explicit knowledge, opportunities, risks and uncertainties, external knowledge management and inhibitors of learning.  Non-structures research patterns in: Knowledge creation, knowledge transfer and knowledge implementation. The study also identified specific areas and research questions on which future research could focus in order to set the right research patterns and fill literature gaps. Value: No critical research was done to explore knowledge related themes, discussed topics and achieved results in an organisational context. Furthermore, this study not only provides an overview, but also performs an analysis that allows for the understanding of past and current research on organisational knowledge, and assessing where future research should be heading.